STRATEGI MENGATASI RAWAN PANGAN - Sri Widodo (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2007)
The lattest issue on insecurity in several areas of Indonesia has revealed many questions on food production, distribution, equality, poverty, shorterm and longterm policies, as well as, the general development policy. Sustainable food security covers, food availability, stability, self reliance, and sustainability. Hierarchically food security can be at global order, regional, national, local, household, and individual